Effects of a Single Hit from the Alpha Hemolysin Produced by Escherichia coli on the Morphology of Sheep Erythrocytes - Jorgensen, Sally E. (1980)
Scanning electron micrographs of sheep erythrocytes showed that attachment of the alpha hemolysin produced by Escherichia coli resulted in the formation of spherocytes, with 10 to 20 small projections spaced relatively evenly over the surface of the erythrocyte membrane. This shape change was induced within 5 min after treatment. If the hemolysin concentration was reduced to a level which would lyse only a fraction of the total erythrocytes, the affected cells were easily identified against a background of normal, unaffected cells. Unlike sodium lauryl sulfate and other amphipathic agents which enter cell membranes and increase their flexibility, low concentrations of hemolysin did not provide protection against hypotonic hemolysis. These findings indicate that the surface projections were not the result of membrane expansion caused by incorporation of hemolysin into the outer portion of the lipid bilayer. The ability of a given amount of hemolysin to release a constant amount of hemoglobin in the presence of increasing concentrations of red cells confirmed that a single hit is sufficient for lysis. These results suggest that a single hemolysin molecule can bind to a sheep erythrocyte and trigger internal reactions which result in the derangement of membrane integrity at multiple sites on the surface. Confirmation of one-hit kinetics indicates that measurement of E. coli hemolysin activity should be carried out at low ratios of hemolysin to erythrocyte to decrease the possibility of multiple hits on a single cell.